Split PO for paging in B5G networks - Agiwal, Mamta; Agiwal, Anil; Maheshwari, Mukesh Kumar; Muralidharan, Shapna (Academic Press, 2022)
Beyond 5G (B5G) wireless networks, imbued with several beams to support high-frequency spectrum, would require enhancements to the current paging monitoring mechanism in Idle mode Discontinuous Reception (IDRX) for improving UE's energy efficiency. The lengthy pre-wakeup and processing overheads in directional IDRX for beam tracking and time-frequency synchronization in every IDRX cycle would result in higher UE's power consumption. Recently, the functioning of Synchronization Signal Block (SSB) has been standardized for synchronization in New Radio (NR) 5G communications. In this article we first highlight inevitability and details of SSB measurements in every IDRX cycle of directional 5G/B5G communication. The UE's power saving reduces substantially due to SSB measurements as the deep sleep duration in every IDRX cycle shrinks. Moreover, during the time gap between periodic SSB transmission(s), the UE can only transit to light sleep. An early indication that can inform UE whether to measure multiple SSB's when paging is expected in an IDRX cycle or continue to deep sleep in absence of paging would be very beneficial in UE's power saving. We propose a novel Split PO Paging (SPOP) mechanism that manifests early indication, avoids unnecessary SSB measurements and reduces UE's pre-wakeup energy overheads. We use Markov chain modeling to analyze SPOP and validate our modeling through simulations. The Proposed SPOP can save more than 40% power compared to IDRX mechanism with elaborate pre wake-up and processing.